2009
DOI: 10.1128/jvi.00427-09
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MicroRNA Targets in the 3′ Untranslated Region as a Mechanism of Retroviral Insertional Activation of Growth Factor Independence 1

Abstract: The non-oncogene-bearing retrovirus SL3-3 murine leukemia virus induces strictly T-cell lymphomas with a mean latency of 2 to 4 months in mice of the NMRI-inbred (NMRI-i) strain. By high-throughput sequencing of retroviral tags, we have identified the genomic region carrying the transcriptional repressor and oncogene growth factor independence 1 (Gfi1) as a frequent target for SL3-3 in the NMRI-i mouse genome. Twenty-four SL3-3 insertions were identified within a 1-kb window of the 3 untranslated region (3UTR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 83 publications
(97 reference statements)
1
17
0
Order By: Relevance
“…15,17,21 Gfi1 protein expression is also regulated by microRNAs. 22 Finally, Gfi1 expression is also regulated at the protein level through ubiquitin-proteasome-mediated degradation. 23,24 Expression of Gfi1 and Gfi1b is therefore tightly regulated at multiple levels.…”
Section: Structure and Expression Regulation Of Gfi1 And Gfi1b Proteinsmentioning
confidence: 99%
“…15,17,21 Gfi1 protein expression is also regulated by microRNAs. 22 Finally, Gfi1 expression is also regulated at the protein level through ubiquitin-proteasome-mediated degradation. 23,24 Expression of Gfi1 and Gfi1b is therefore tightly regulated at multiple levels.…”
Section: Structure and Expression Regulation Of Gfi1 And Gfi1b Proteinsmentioning
confidence: 99%
“…Sh2d1a , Cask , Mr1 , and Stx6 showed the highest upregulation in the tumors where they were found as integrations, indicating an activating effect of the integrated retrovirus on these genes. The expression of Notch1 , Myc , Rasgrp1 , Rras2 and the D-type cyclines, which are major common integration target in many MLV induced lymphomas [20,22,28,30], remained unchanged in both overall gene expression and in the individual tumors where they were found as integrations. Although our results indicate that the presence of a virus in the vicinity of a gene does not always alter its expression, we cannot exclude whether or not there is an oncogenic effect of the integrations on protein stability or alternative splicing, as we only analyzed the summarized gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Dabrowska et al demonstrated how MMLV insertion mutagenesis overcomes miR targeting to activate Gfi1 expression [69]. While insertion sites in the Gfi1 3′ UTR were known to lead to increased transcript levels [2,70], these insertions also truncate the Gfi1 transcript to eliminate binding sites for a number of miRs, including miR-155 and miR-10a [69].…”
Section: Gfi1 In Lymphoid Leukemiamentioning
confidence: 99%